2020
DOI: 10.1007/s12182-020-00496-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoparticles on reservoir wettability alteration: a critical review

Abstract: A novel concept of treating oil reservoirs by nanofluids is being developed to improve oil recovery and reduce the trapped oil in hydrocarbon reservoirs. Nanoparticles show great potential in enhancing oil recovery under ambient conditions. In this paper, the approaches of wettability alteration by using nanofluid, stability of nanofluids, and the most reliable wettability alteration mechanisms associated with variant types of nanoparticles have been reviewed. Moreover, the parameters that have a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 143 publications
(136 reference statements)
1
57
0
Order By: Relevance
“…We can estimate the contact radius of the droplet r by noting that F = (2γ/R)πr 2 , where γ = 50 mN m −1 is the water-oil interfacial tension as measured using the pendant drop's method and 2γ/R is the Laplace pressure inside the microdroplet. At the maximum loading F = 10 nN, r ≈ 0.5 µm which is much larger than the size of the nanoparticles and similar in size to the spacing between nanoparticles aggregates.…”
Section: Reduction In Oil Droplet Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can estimate the contact radius of the droplet r by noting that F = (2γ/R)πr 2 , where γ = 50 mN m −1 is the water-oil interfacial tension as measured using the pendant drop's method and 2γ/R is the Laplace pressure inside the microdroplet. At the maximum loading F = 10 nN, r ≈ 0.5 µm which is much larger than the size of the nanoparticles and similar in size to the spacing between nanoparticles aggregates.…”
Section: Reduction In Oil Droplet Adhesionmentioning
confidence: 99%
“…Suspensions of nanoparticles or nanofluids have many important technological applications, including for enhanced heat transfer and oil recovery processes. 1,2 The wetting properties of surfaces are altered when nanoparticles adsorb onto the surface; 3 for example, with silica and other metal oxide nanoparticles, the surface becomes more water-wettable or hydrophilic. This greatly improves the heat transfer rates during boiling by preventing air bubbles (which conduct heat poorly) from accummulating on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of NF can be measured by various means, such as sedimentation and centrifugation methods, spectral absorbency analysis, Zeta potential measurements [ 27 ] or even visual inspection. A range of factors can affect the stability of NF, such as the preparation method used, the temperature, the salinity of the base fluid, the concentration of the NPs, the size of the NPs, the permeability of the porous media, and the injection rate [ 8 , 33 , 34 , 35 , 36 , 37 , 38 ]. The challenge of achieving stability can be addressed by adopting correct preparation procedures and in some cases the use of suitable stabilizers such as polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), and/or adjusting the pH value of the solution [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators [ 8 , 30 , 39 ] have reported an increase in oil recovery beyond that of conventional means via the injection of NF into oil-wet carbonate reservoirs. Most of the NF EOR mechanisms that have been reported involve structural disjoining pressure (SDP) [ 23 , 35 , 40 , 41 ], plugging of pore channels [ 35 ], viscosifying the injectants and reducing oil viscosity and IFT [ 42 ], changes in wettability [ 31 , 42 , 43 , 44 ], and preventing the precipitation of asphaltene [ 26 , 45 ]. Young et al [ 46 ] reported the role of anions in the determination of Si/SiO 2 surfaces water wettability and how the choice of solvents/dispersant can affect the anion rate of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Farad et al (2020) found that hydroxyl-functionalized silica-based nanofluids altered the wettability from intermediate-wet to stronger water-wet as the concentration of nanoparticles increased. Eltoum et al (2020) summarized and analyzed different kinds of nanoparticles on wettability alteration.…”
Section: Introductionmentioning
confidence: 99%